Adapting or Freezing? Ideological Reactions of Communist Regimes to a Post-Communist World - Alexander Dukalskis; Johannes Gerschewski (Government and Opposition, 2020)
This article studies the ideological reactions of communist regimes to the advent of a post-communist world. It examines two cases of reformed communist regimes (China and Vietnam) with two relatively unreformed cases (North Korea and Cuba) to understand different legitimation strategies employed during and after the downfall of the Soviet Union. Theoretically, the article compares two ideal-type approaches to ideology in autocratic regimes. The first approach emphasizes semantic `freezing' over time. The consistency and coherence of ideology is underlined. The second approach argues that the success of an ideology lies in its ability to be a dynamic, adaptive force that can react with changing circumstances. Four parameters help to distinguish the freeze-frame end from the adaptation pole: (1) the autonomy over semantic changes, (2) the timing, (3) the velocity and (4) the distance that an ideology moves. Using qualitative case-based analysis that is enriched with quantitative text analysis of communist party documents, this article compares these contending conceptions of ideology with each other in the four cases. Sharing similar starting conditions in the 1970s, the article shows how China and Vietnam harnessed a flexible legitimation strategy while North Korea and Cuba adopted a comparatively rigid legitimation approach.
Keywords: 330; authoritarianism; communism; legitimation; ideology; China; North Korea; Cuba; Vietnam